Strategi Peningkatan Kinerja Karyawan, Digitalisasi Sistem Persediaan, dan Pemasaran Berbasis Komunitas pada Tata Kelola Usaha Bengkel - Daspar, Daspar; Zulfa Zakiatul Hidayah; Indra Permana; Shafiera Lazuarni; Aulia Aryani, Annisa (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
This Community Service activity was carried out to improve the business governance of the Brothers Workshop in the Waluya area, Cikarang, which faced problems in the form of the absence of a Standard Operating Procedure (SOP) for performance, a manual inventory recording system, and limited marketing to local customers. This condition has an impact on low operational efficiency, less than optimal inventory management, and limited marketing reach. The business governance strengthening program is carried out through the stages of socialization, training, mentoring, implementation of a digital inventory system, workspace arrangement with the 5S method, activation of Google Business Profile, and evaluation of program implementation. The results of the activity showed an increase in the understanding and skills of partners in implementing operational SOPs, the use of digital inventory systems for more accurate stock recording, and the use of digital media as a means of community-based marketing. The implementation of the program has a positive impact on operational efficiency, order of inventory management, improvement of service quality, and business competitiveness. Thus, this activity contributes to more professional, effective, and sustainable workshop management in facing business challenges in the digital era.